2010
DOI: 10.1021/nn102064c
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Separation of Nanoparticles with Ultrathin Porous Nanocrystalline Silicon Membranes

Abstract: Porous nanocrystalline silicon (pnc-Si) is a 15 nm thin freestanding membrane material with applications in small-scale separations, biosensors, cell culture and lab-on-a-chip devices. Pnc-Si has already been shown to exhibit high permeability to diffusing species and selectivity based on molecular size or charge. In this report we characterize properties of pnc-Si in pressurized flows. We compare results to long-standing theories for transport through short pores using actual pore distributions obtained direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
125
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 42 publications
8
125
0
Order By: Relevance
“…Surprisingly, we discovered that the 30-nm membranes exhibited lower stall pressures than the 15-nm membranes (Table S1), indicating that thickness was not the only variable that determined stall pressures. By characterizing the pore distributions of the two membranes, we were able to calculate a significantly higher hydraulic permeability for the 30-nm membrane (Table S2) (18). Whereas the porosities of the 15-and 30-nm membranes were similar, it has been shown that larger pores naturally form in thicker membranes due to looser geometric constraints (19).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, we discovered that the 30-nm membranes exhibited lower stall pressures than the 15-nm membranes (Table S1), indicating that thickness was not the only variable that determined stall pressures. By characterizing the pore distributions of the two membranes, we were able to calculate a significantly higher hydraulic permeability for the 30-nm membrane (Table S2) (18). Whereas the porosities of the 15-and 30-nm membranes were similar, it has been shown that larger pores naturally form in thicker membranes due to looser geometric constraints (19).…”
Section: Significancementioning
confidence: 99%
“…The electric field strength (8 × 10 5 V/m) and a 15-nm-thick membrane require a transmembrane voltage of only 12 mV. Low membrane resistance compared with all other resistances in the system has been observed for diffusive transport through pnc-Si (17,18,20,22). In these studies, the ultrathin dimension of the membrane results in a transmembrane resistance to diffusion that can be neglected compared with bulk resistances.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…So far, the main methodologies for separation of nanoparticles include ultracentrifugation, eld ow fraction, electrophoretic, magnetic and membrane separation methods. 35,[38][39][40][41][42] We found that the as-prepared WCNWs could be fabricated into membrane to be used for separate Au nanospheres with different sizes of 10 and 50 nm from solution using the handmade setup (Fig. S7, † 5a).…”
Section: Separation Of Au Nanospheresmentioning
confidence: 99%